Sudut Pandang Berbeda dan Baru dalam Perilaku Konsumen: Review Buku Consumer.ology dari Philip Graves - Soetam Rizky Wicaksono (Jurnal Sosioteknologi, 2023)
This article provides a comprehensive review and analysis of Philip Graves' "Consumer.ology", a seminal work that offers a fresh perspective on consumer behavior. The book challenges traditional market research theories and aligns with certain psychological and sociological theories, emphasizing the importance of environmental influences, unconscious factors, and social context in shaping consumer behavior. The article delves into the "Crowd Factor" in consumer behavior, a concept particularly relevant in today's digital age where online commerce dominates and celebrity endorsements, along with viral trends, significantly sway consumer behavior. The article also explores Graves' AFECT criteria, a unique perspective that challenges traditional market research theories. The insights from the book are particularly relevant for marketers and businesses in the digital age, providing valuable insights for crafting more effective strategies to influence consumer behavior. The article concludes that "Consumer.ology" is a valuable resource for anyone interested in understanding consumer behavior, offering a fresh perspective and valuable insights for marketers and researchers.